The first record of the chimaeroid genus Edaphodon (Chondrichthyes, Holocephali) from Antarctica (Snow Hill Island Formation, Late Cretaceous, James Ross Island) - Gouiric Cavalli, Soledad (2015)
A new species of an edaphodontid holocephalian, Edaphodon snowhillensis, sp. nov., is described based on a complete dentition collected in the late Campanian Herbert Sound Member of the Snow Hill Island Formation of James Ross Island, Antarctica. The dentition consists of paired vomerine, mandibular, and palatine tooth plates, which are almost completely preserved. The new species is characterized by a unique character combination out of which the presence of a subquadrangular vomerine tooth plate and a horse-hoof-shaped anterior outer tritor in the mandibular tooth plates appear to be unique characters among the edaphodontids. Edaphodon snowhillensis, sp. nov., represents the most complete dentition of a holocephalian fish from the Southern Hemisphere and the earliest record of the genus Edaphodon from the Antarctic continent and the Weddellian Biogeographic Province. Also, E. snowhillensis, sp. nov., is the southernmost specimen of this genus and according to the size of the tooth plates is one of the largest chimaeroid fish known.